Morphological and Compositional Design of Pd–Cu Bimetallic Nanocatalysts with Controllable Product Selectivity toward CO2 Electroreduction. Issue 7 (27th December 2017) - Zhu, Wenjin; Zhang, Lei; Yang, Piaoping; Chang, Xiaoxia; Dong, Hao; Li, Ang; Hu, Congling; Huang, Zhiqi; Zhao, Zhi‐Jian; Gong, Jinlong
Abstract: Electrochemical conversion of carbon dioxide (electrochemical reduction of carbon dioxide) to value‐added products is a promising way to solve CO2 emission problems. This paper describes a facile one‐pot approach to synthesize palladium–copper (Pd–Cu) bimetallic catalysts with different structures. Highly efficient performance and tunable product distributions are achieved due to a coordinative function of both enriched low‐coordinated sites and composition effects. The concave rhombic dodecahedral Cu3 Pd (CRD‐Cu3 Pd) decreases the onset potential for methane (CH4 ) by 200 mV and shows a sevenfold CH4 current density at −1.2 V (vs reversible hydrogen electrode) compared to Cu foil. The flower‐like Pd3 Cu (FL‐Pd3 Cu) exhibits high faradaic efficiency toward CO in a wide potential range from −0.7 to −1.3 V, and reaches a fourfold CO current density at −1.3 V compared to commercial Pd black. Tafel plots and density functional theory calculations suggest that both the introduction of high‐index facets and alloying contribute to the enhanced CH4 current of CRD‐Cu3 Pd, while the alloy effect is responsible for high CO selectivity of FL‐Pd3 Cu. Abstract : Pd–Cu bimetallic nanocatalysts are synthesized through a rational designed route. Thanks to the controllable composition and enriched high‐index surfaces, highly efficient activity and tunable product distribution toward CO2 electroreduction are achieved. In addition, a clear insight into the enhanced mechanism of catalytic performance is elucidated.